Concomitant Medial Patellofemoral Ligament Reconstruction, Tibial Tubercle Osteotomy, Trochleoplasty, and Osteochondral Autograft Transfer to the Patella - Jewel A. Stone, B.S., B.A.; Evan P. Shoemaker, B.A.; Luke V. Tollefson, B.S.; Erik L. Slette, M.D.; Nathan J. Jacobson, M.D.; Robert F. LaPrade, M.D., Ph.D. (Arthroscopy Techniques)
Recurrent patellar instability increases the risk of developing patellofemoral arthritis, among other complications. Chronic patellar instability frequently evolves into a debilitating issue that necessitates surgical intervention. Lateral patellar dislocation caused by a torn medial patellofemoral ligament (MPFL) is commonly addressed with an isolated MPFL reconstruction. Risk factors of MPFL graft failure and further patellar instability include patella alta and elevated tibial-tubercle trochlear-groove distance, which are addressed by a tibial tubercle osteotomy with distalization and/or medialization. Trochlear dysplasia is addressed through a sulcus-deepening trochleoplasty. An osteochondral autograft transfer is used to transfer healthy cartilage from a lesser-articulating surface to address areas of small cartilage defects. We describe a concomitant MPFL reconstruction, tibial tubercle osteotomy, trochleoplasty, and osteochondral autograft transfer to address chronic recurrent lateral patellar instability, patella alta, trochlear dysplasia, and a full-thickness patellar osteochondral defect.